Second All-Union Programming Conference - Meshchikov, Valery F.; Pavlovskaya, Irina Yu; Cheremnykh, Natalia (2020 Fifth International Conference “History of Computing in the Russia, former Soviet Union and Council for Mutual Economic Assistance countries” (SORUCOM), 2020)
The paper presents the history of organization and holding of the Second All-Union Programming Conference (VKP-2) - a notable event in the life of the programming society in the period of establishing of computer science and one of the most popular professions of the future. The work uses on materials from the Digital Archive of the Academician A.P. Ershov, one of the founders of the national programming.